Health Communication As An Approach In Adolescent Counseling: An Exploration Of Mental Health Practitioners - Vina Dartina; Uud Wahyudin; Siti Nuriah (Journal of Education and Counseling (JECO), 2025)
The issue of mental health among adolescents is becoming increasingly significant in the educational and social realms, as many adolescents face emotional distress without the support of a safe space to understand and manage their feelings. This study aims to explore the application of health communication principles in adolescent counseling practices, both by practitioners in formal settings such as schools and non-formal communities. Using a qualitative method with a case study approach, data was collected through in-depth interviews with three informants, namely a community mental health activist, an academic in the field of counseling guidance, and an adolescent who acted as a counselee. Findings from thematic analysis show that health communication is not only used to convey educational information, but also to build interactions that are empathic, participatory, and in accordance with the context of the counselee's life. The practice is realized through the use of familiar language, supportive gestures, and easy-to-understand analogies, such as "a tank of emotions" or "a body that asks for help." Communication is understood as a medium of recovery that allows for emotional validation, psychosocial assistance, and space for personal reflection. The results of this study confirm that health communication principles can enrich the adolescent counseling process, especially in strengthening trust and encouraging a deeper recovery process. This approach deserves to be developed in community-based counseling services that are adaptive to the emotional needs of today's adolescents.